The role of the church through MDT ministry in poverty alleviation - Maya Djawa; Arriyon Prata; Sulistyastuti Sutomo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Poverty remains a challenge in Kupang City and Kupang Regency, East Nusa Tenggara Province, requiring special attention from the government and society, including the church. This study analyzes what roles do churches play through the MDT Ministry in poverty alleviation, what strategies are utilized to implement its service programs, what are the impacts on poverty issues for beneficiaries, and what challenges are encountered in poverty reduction efforts. This study employed data collection techniques: interviews with 12 informants consisting of MDT Ministry administrators, members, and beneficiaries, observation, and documentation. The data were transcribed into Microsoft Word documents and subsequently imported into NVivo 11 for thematic coding. Word frequency analysis was conducted using Word Cloud and Word Frequency Query tools to identify the most frequently occurring words to determine the theme. To analyze each theme, the researchers utilized the Mind Map feature in NVivo 11 to create visual representations, which were then described and interpreted. The findings reveal that the role of the church through MDT Ministry implements five strategic programs: ecumenical solidarity through inter-church collaboration and unity; physical needs fulfillment through congregation needs surveys and provision of essential needs; spiritual needs fulfillment through prayer, worship, and biblical guidance; social welfare services through counseling, medical care, and support for vulnerable groups; and youth leadership development through training and mentorship, similar to the Luke 9:10-17 account of Jesus feeding the 5,000 people. These programs impact inter-denominational harmony that have the same concern for the poverty issue, family welfare, spiritual transformation, and youth unity, although challenges remain. This study contributes valuable insights for church practitioners, academics, and social institutions on effective strategies and challenges in implementing church ministries programs.